Reliabilitas Dokumen Injil Sinoptik - Henry Henry (STT KINGDOM BALI, 2022)
Many people think that the synoptic gospel documents contain many errors, are of doubtful authenticity, have been distorted and also contradict each other. So the reliability of the synoptic gospels is questioned. Is that true? Of course all that is not true. This article will provide answers to these accusations and misunderstandings.